On Meaning and Function of the Painting Apparition of the Sibyl to Emperor Augustus by Paris Bordone - Nazarova, Olga A.; Gaynullina, Regina R. (Actual Problems of Theory and History of Art, 2021)
This paper reconsiders the meaning and function of the painting The Apparition of the Sibyl to Emperor Augustus by Paris Bordone by examining its subject in the light of the medieval interpretations of Tiburtine Sibyl’s prophecy to Octavian Augustus. These interpretations expressed in an array of texts, have been molded by the world view at the beginning of the 16th century into an eschatologicaly endowed concept of the Last Emperor, a spiritual and political leader, who, like Emperor Augustus, stands at the turn of the era, and is supposed to prepare mankind for the end of the world. This concept influenced the political ideology of the time in that European sovereigns were identified with the Last Emperor. Among them Emperor Charles V Habsburg stands out, who was addressed by his contemporaries both as New Augustus, and as the Last Emperor, especially after his victory over the Protestants at Mühlberg. The striking visual affinity between the architectural setting of the painting and the decorations of Charles V’s triumphal entries, the multiple historical connections between Charles V, the city of Augsburg, and Paris Bordone’s career support the hypothesis, that the painting is an allegorical representation of Charles V as New Augustus, and the Last Emperor, and was commissioned in Augsburg to celebrate his triumphal arrival to the 1548 Imperial Diet of Augsburg.